A Classroom Based Analysis Of Teaching Methods For Mathematics Subject: A Study Based In Leading Chinese Region - Nuenjiya; chakkaravarthy, Midhun; Agarwal, Nidhi (Cuestiones de Fisioterapia, 2023)
This research set out to examine how well chinese middle school students understood the mathematics curriculum and to draw comparisons between them. Implications for mathematics instruction are substantial since the findings show that maths instructors in the two nations have vastly differing views on pedagogical matters. Still, many chinese teachers place a premium on ensuring their students understand mathematical ideas and processes via the use of less adaptable, more conventional methods of instruction. Teachers of mathematics in china employed a broad range of activities designed to foster students' critical thinking, creativity, and independence in the classroom. There are benefits and drawbacks to every possible strategy. Teachers in one nation could modify their methods to compensate for those in another. From a global standpoint, there has been very little study on mathematics education in china and other east asian countries. Finding strategies to improve mathematics education in western nations is of interest to many western academics. Teachers of mathematics in china, on the other hand, have an obligation to ensure that studies like this contribute to the improvement of mathematics education in their own country. If the researcher wants to know where the researcher stand and how the researcher may improve, the researcher should compare their system to other nations'. The study's author can now say with authority that it is high time for a comprehensive review of china's mathematics education system. This new style of thinking has also prompted some chinese towns to revise their mathematics curricula. In order to get insight into mathematics education, the researcher reviews the last 20 years of research in these fields.